use of electronic platforms in the educational process from by faculty members in College of Arts, University of Basra: survey study - Taha Abbood, Lect.Tariq (Basra studies journal, 2022)
The research aims to identify the role of electronic platforms in developing the educational process and identifying the viewpoint of faculty members in using electronic platforms and the problems and difficulties they face when using these platforms, and the survey approach was adopted in the practical aspect and in the theoretical aspect, the documentary approach was adopted using traditional and electronic sources of information. The questionnaire tool was adopted as a main tool in collecting information and data of research, and the research community included members of the teaching staff at the University of Basra, College of Arts. The research came out with conclusions, including:- - There are some obstacles and difficulties facing faculty members when they use electronic platforms in education, including weak internet and power cuts -The most used electronic platforms in the educational process are google class room and google meet, and the least used platform is the FCC platform. The research came up with several proposals, including: - The necessity of holding training courses and remote video conferences for faculty members on how to use electronic platforms in the educational process. - The need to provide a strong and fast Internet on a continuous basis to meet the needs of teachers and students and to eliminate the obstacles they face.